Thermal properties and dielectric behaviour of poly(ethylene oxide)/polyacrylate with and without salt / Amirah Hashifudin - Hashifudin, Amirah (2016)
Immiscible blends of poly(ethylene oxide) (PEO)/polyacrylate (PAc) were reported on enhancement of conductivity but silent on the mechanical properties of the materials. Hence, in this study, by simple melt mixing of PEO/PAc, miscible blends can be prepared. Mechanical properties of the miscible blends are normally additives to the parent polymers. Blends of salt-free PEO/PAc, PEO/PAc 100/0, 85/15, 75/25, 50/50, 25/75 and 0/100 added with lithium perchlorate (UCIO4) of concentrations (Fs) from 0.005-0.30 (w/w) were prepared via solution casting method. Thermal properties of the salt-free and salt-added of the PEO/PAc blends were characterised by differential scanning calorimetry (DSC) and polarized optical microscope (POM). The impedance spectroscopy (IS) and dynamic mechanical analysis (DMA) used to study the dielectric behaviour of the blends. Miscibility of the salt-free PEO/PAc blend is marked by the presence of a single composition dependent glass transition temperature (rg) and the continual suppression of the melting temperature (Tm), equilibrium melting temperature (rm°) and degree of crystallinity {X) of PEO with ascending PAc content. A reduction in the rate constant (KA) with increasing PAc content evaluated using Avrami equation indicates restricted crystallization of PEO in the homogeneous PEO/PAc blend. Meanwhile, miscibility of the PEO/PAc/LiC104 blend is evident in the presence of a single Tg and a decrease in the radial spherulite growth rate of PEO. Morphology result shows that the as-prepared blend with 15 wt% PAc displays co-continuous amorphous region transverse through the entire PEO matrix. No crystal is observed when PAc content is > 30 wt%. Coarsening of PEO lamellae and distorted morphology of PEO spherulites spotted with dark regions are observed in the neat PEO and the PEO/PAc 85/15 blend when Fs = 0.02 of LiC104 is added. PEO/PAc 85/15 blend doped with 7S=0.12 of LiC104 exhibits the highest DC conductivity (obc) of 2.9 x 10"5 S cm"1 suggesting firstly the preferential coordination of the salt to PEO as compared to PAc and secondly the amorphous phase of PEO forms the percolation pathway for ion-transport in the blend. A relaxation peak is observed at the high frequency of the plot between the imaginary dielectric modulus (M") and frequency. Shifting of the relaxation peak towards higher frequency with increasing salt content reflects the shortening of the relaxation time of PEO leading to an increase in the ionic charge carrier. DMA analysis shows a high £' value (in the range of 108 - 109 Pa) for neat PEO impling that it has a high density of chain alignment. All the compositions of both the salt-free and the salt-added blends behave dominantly elastic or solid-like as evident from the higher value of E as compared to E . However, the elastic characteristic of the salt-added blend becomes more viscous liquid-like as the concentration of salt is increased.